Trends and Opportunities in Social Entrepreneurship Education Research - Arantxa Azqueta; Roberto Sanz-Ponce; Margarita Núñez-Canal (Administrative Sciences, 2023)
The objective is analyzing the trends in Social Entrepreneurship Education as a multidisciplinary research field. A systematic review of the literature on the intersection: Education and Social Entrepreneurship, with the support of scientific literature and a careful search methodology. It collects articles from the WOS Core collection database published between 2000 and 2022. A total of 367 articles are analyzed to answer the three research questions. The results of the analysis are twelve dimensions identified according to the literature in the field of social entrepreneurship education; after using lexicometric analysis and Iramuteq software, the main trends on the topics are found and discussed and the relationship of terms and concepts in the abstract and title text of the analyzed articles is shown, showing the frequency, importance of linkage, and co-occurrences of lexical units. Six clusters of nodes and related terms are confirmed: entrepreneur, development and innovation, education, entrepreneurial university, context, and types of study. These clusters show the concern for the field of study of social entrepreneurship education and the need to find a consensus on the concept of an entrepreneur and on what is social entrepreneurship in education. The wide range of topics, dispersed and fragmented, continues to offer opportunities for specificity.